Reforming of the ukrainian educational system in the context of transborder integration into the world academic space - Tolochko, Svitlana (ScienceRise: Pedagogical Education, 2020)
This article analyzes the experience of forming of the world educational space in the context of transborder integration. The world practice of solving educational problems is considered, essential characteristics of integration processes for further implementation in the educational process of the national educational system are revealed. The reports of the Davos Economic Forum, the INSEAD International Business School, Cornell University and the World Intellectual Property Organization, the Roman Club, the UN Human Development Indexes and Indicators, the World Education Forum, and the Cambridge Assessment non-governmental organization are analyzed. It is confirmed, that reforming of the Ukrainian educational system in the process of integration into the world academic space is due to the development and implementation of the legislative and regulatory documentation in the educational and scientific process of domestic educational institutions. The interim results of the national profile ministry on reforming Ukraine’s education system into the academic world are characterized: priorities for 2019 in reforming of Ukraine’s educational system in the context of transborder integration and current plans - "To do list" changes - that will be implemented in the fields of education, science and innovation theory. It is stated, that these tasks actualize the increase of HEA and STD teachers’ professional and pedagogical competence. Thus, the Model educational program of organization and carrying out pedagogical workers’ advanced training in postgraduate pedagogical education establishments in the profile of coaches’ and primary school teachers’ basic competences include the following: andragogic, vocational-pedagogical, socio-civic, linguistic and communicative information-digital. It is determined, that the conducted analysis actualized another important teacher’ competence - scientific and methodical, its definition in the author’s vision is formulated. The problems of human resources and labor migration in the context of contemporary globalization challenges and the cross-border integration of Ukraine into the world academic space are investigated and recommendations are given for their solution